1997
DOI: 10.1021/jf9603137
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Validated Method for the Determination of Provitamin A Carotenoids in Indonesian Foods of Different Maturity and Origin

Abstract: Provitamin A carotenoids were measured using a validated high-performance liquid chromatography method in a number of selected leafy vegetables of different maturity and origin, sweet potatoes, and mangos from Indonesia. Mean provitamin A content per 100 g of edible portion was 492 retinol equivalents (RE) for water spinach (Ipomoea aquatica; n = 8), 640 RE for spinach (Amaranthus viridis; n = 8), 1776 RE for cassava leaves (Manihot utulissima; n = 8), 992 RE for papaya leaves (Carica papaya; n = 9), 1889 RE f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 19 publications
2
56
0
2
Order By: Relevance
“…High levels of β-carotene in Sauropus androgynus leavesellow color of shank in broiler chickens fed diets supplemented with SALE. Hulshof et al (1997) reported that Sauropus androgynus leaves contained as much carotene 12.657 µg per 100 g of fresh leaves (Hulshof et al, 1997). plus 0 g SALE; P1 = 19% protein plus 4.5 g SALE/kg diet; P2 = 17% protein plus 4.5 g SALE /kg; P3 = 15% protein plus 4.5 g SALE/kg; P4 = 19% protein plus 9 g SALE/kg; P5 = 17% protein plus 9 g SALE /kg; P6 = 15% protein plus 9 g SALE/ kg…”
Section: Carcass Qualitymentioning
confidence: 99%
“…High levels of β-carotene in Sauropus androgynus leavesellow color of shank in broiler chickens fed diets supplemented with SALE. Hulshof et al (1997) reported that Sauropus androgynus leaves contained as much carotene 12.657 µg per 100 g of fresh leaves (Hulshof et al, 1997). plus 0 g SALE; P1 = 19% protein plus 4.5 g SALE/kg diet; P2 = 17% protein plus 4.5 g SALE /kg; P3 = 15% protein plus 4.5 g SALE/kg; P4 = 19% protein plus 9 g SALE/kg; P5 = 17% protein plus 9 g SALE /kg; P6 = 15% protein plus 9 g SALE/ kg…”
Section: Carcass Qualitymentioning
confidence: 99%
“…On each occasion, portions were collected for analysis over 3 consecutive days, which corresponded to the 3-d menu cycle. Duplicate samples of the meals were pooled per treatment group per 3 consecutive days, frozen at Ҁ20°C, and later shipped (in dry ice) to the Division of Human Nutrition and Epidemiology for analyses of fat, protein, dietary fiber, ash, dry matter, iron, retinol, and carotenoids (20,21). Carbohydrate content was calculated by the difference from the analyzed content of the above substances.…”
Section: Duplicate Food Portionsmentioning
confidence: 99%
“…The limit of detection (LOD), calculated as LOQ divided by 2.5 (Hulshof et al, 1997) was 0.0156 μg/mL. The precision of the instrumental technique (n=10) was evaluated by analyzing standard samples prepared by serial dilution within the working range each day for about two weeks.…”
Section: Validation Of the Established Methods Linearity And Calibratimentioning
confidence: 99%
“…This was performed six times (n=6). The limit of detection (LOD) defined as amount of the carotenoid, resulting in a peak height three times the baseline noise (Hulshof et al 1997) was calculated.…”
Section: Peak Identification and Quantificationmentioning
confidence: 99%
See 1 more Smart Citation